Maximizing Energy Recovery from Waste Tires Through Cement Production Optimization in Togo—A Case Study - Mona-Maria Narra; Essossinam Beguedou; Satyanarayana Narra; Michael Nelles (Waste, 2025)
The cement industry faces increasing energy costs and environmental pressures, driving the adoption of alternative fuels derived from waste materials. In Togo, approximately 350,000 t of end-of-life tires (ELT) are generated annually, creating significant environmental and health hazards through uncontrolled disposal and burning practices. This study investigated the technical feasibility and economic viability of incorporating waste tires as an alternative fuel in cement manufacturing. Tire-derived fuel (TDF) performance was evaluated by comparing pre-processed industrial tires with unprocessed ones, focusing on clinker production loss, elemental composition, heating values, and bulk density. The results demonstrate that TDF exhibits superior performance characteristics, with the highest heating values, and meets all the required specifications for cement production. In contrast, whole tire incineration fails to satisfy the recommended criteria, necessitating blending with conventional fuels to maintain clinker quality and combustion efficiency. The investigation revealed no significant adverse effects on production processes or clinker quality while achieving substantial reductions in nitrogen and sulfur oxide emissions. The experimental results were compared with the theoretical burnout times to optimize the shredding operations and injection methods. However, several challenges remain unaddressed, including the absence of streamlined handling processes, limited understanding of long-term ecological and health impacts, and insufficient techno-economic assessments. Future research should prioritize identifying critical aging points, investigating self-rejuvenating behaviors, and quantifying long-term environmental implications. These findings provide a foundation for developing computational models to optimize the mixing ratios of alternative and fossil fuels in cement manufacturing, offering significant environmental, economic, and societal benefits for the cement industry.